Reciente Reforma del Mercado Laboral Español (Apuntes Breves Sobre el Nuevo Régimen Jurídico del Despido) - Miñambres Puig, César (2016)
The economic crisis faced by Spain, forced the Spanish government to conduct several reforms in labor legislation in order to address the high rates of unemployment, which led greater flexibility about worker protection, reflected more intensively about dismissal labor. Thus, this article will develop the most important edges of this new legal regime of dismissal according to Spanish labor regulations.